Characterization of the particulate emissions from the BP Deepwater Horizon surface oil burns. Issue 1 (15th June 2016) - Gullett, Brian K.; Hays, Michael D.; Tabor, Dennis; Wal, Randy Vander
Abstract: Sampling of the smoke plumes from the BP Deepwater Horizon surface oil burns led to the unintentional collection of soot particles on the sail of an instrument-bearing, tethered aerostat. This first-ever plume sampling from oil burned at an actual spill provided an opportunistic sample from which to characterize the particles' chemical properties for polycyclic aromatic hydrocarbons (PAHs), organic carbon, elemental carbon, metals, and polychlorinated dibenzodioxins/dibenzofurans (PCDDs/PCDFs) and physical properties for size and nanostructure. Thermal–optical analyses indicated that the particulate matter was 93% carbon with 82% being refractory elemental carbon. PAHs accounted for roughly 68 μg/g of the PM filter mass and 5 mg/kg oil burned, much lower than earlier laboratory based studies. Microscopy indicated that the soot is distinct from more common soot by its aggregate size, primary particle size, and nanostructure. PM-bound metals were largely unremarkable but PCDD/PCDF formation was observed, contrary to other's findings. Levels of lighter PCDD/PCDF and PAH compounds were reduced compared to historical samples, possibly due to volatilization or photo-oxidation. Graphical abstract: Highlights: Particles from the Deepwater Horizon at-sea oil burn plumes were captured and analyzed. PAH levels were lower than from published laboratory simulations. Soot particles had distinctive size and structure from common soot, suggesting increased absorption and scattering. PCDD/PCDF levels were lower than previous measurements likely due to particle and volatile loss.